2010
DOI: 10.1007/s00404-010-1675-y
|View full text |Cite
|
Sign up to set email alerts
|

Ring pessary for all pelvic organ prolapse

Abstract: The ring pessary fitting can be attempted in all POP cases irrespective of stage. Short vaginal length <6 cm and wide introitus >4 fingerbreadths were the risk factors for unsuccessful fitting. It has an acceptable continuation rate and manageable adverse events. The self-care of pessary is an important strategy to minimize adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 14 publications
1
50
0
Order By: Relevance
“…Thirteen papers discussed complications related to pessary size. [20][21][22][23][24][25][26][27][28][29][30][31] By combining the data in both case reports and case studies, we found that the most frequent complications were: vaginal discharge, bleeding, vesicovaginal fistula, erosion, ulceration, and foul odor (Table 1). We graded the reported complications using the Clavien-Dindo classification (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen papers discussed complications related to pessary size. [20][21][22][23][24][25][26][27][28][29][30][31] By combining the data in both case reports and case studies, we found that the most frequent complications were: vaginal discharge, bleeding, vesicovaginal fistula, erosion, ulceration, and foul odor (Table 1). We graded the reported complications using the Clavien-Dindo classification (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…A ring pessary (Chinda Dispensary Registered Ordinary Partnership, Bangkok, Thailand) was used. The detail of this pessary was described in our previous study [2]. Retrospective observational study was conducted that was approved by the Institutional Review Board of the Faculty of Medicine, Chulalongkorn University.…”
Section: Methodsmentioning
confidence: 99%
“…Successful fitting was defined as follows: (1) a patient who continued the pessary use for more than 2 weeks and (2) a patient who had pessary expulsion and was refitted with a new size of pessary at the second visit and continued use for more than 2 weeks. Patients who discontinued pessary within the first 2 weeks and were not able to be refitted were categorized as unsuccessful fitting [2]. Pessary care techniques were explained to the patients and caregivers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the predictors of unsuccessful fitting have been inconsistent among studies. The predictors include a short vagina and wide vaginal hiatus [9, 13, 14], genital hiatus/total vaginal length (GH/TVL) ratio >0.8 [11], lower prolapse Pelvic Organ Prolapse Quantification system (POP-Q) stage [11], posterior wall prolapse [17], previous prolapse repair and hysterectomy [10, 12, 1416], coexistent stress urinary incontinence [16], increased parity [10], age 65 years or younger [11], and smoking [11]. …”
Section: Introductionmentioning
confidence: 99%